MK2: On water valuation - Béné, Christophe; Dubois, Mark; Yumiko, Kura; Hooi Bing, Chin; Samonn, Mith; Suan Pheng, Kam (2009)
This project is about assessing the value of water in its various uses.It includes an assessment of water needs for major water uses and features the application of quantitative and qualitative valuation techniques to estimate costs and benefits associated with different water management strategies and scenarios. Water valuation means expressing the value of water-related goods and services so as to inform sharing and allocation decisions.It features quantitative and qualitative approaches and considers relationships between interconnected and interdependent water uses. Valuation is seen as essential to well-informed water resource management. Valuation will support a structured mechanism of multi-stakeholder dialogues, helping stakeholders to express their values and perceptions on the use and management of water resources.